ON SOME NEW SEQUENCE SPACES OF NON-ABSOLUTE TYPE - Zeren, Suzan; Bektas, Cigdem A. (Inst Applied Mathematics, 2014)
In this paper, we define the new sequence spaces c(0)(lambda)(u), c(lambda)(u) and l(infinity)(lambda)(u), where lambda = (lambda(k))(k=0)(infinity) is a strictly increasing sequence of positive reals tending to infinity, u = (u(n)) is a sequence of complex numbers. A transforms of these spaces are in the spaces c(0)(u), c(u) and l(infinity)(u), respectively. We also establish some inclusion relations between these spaces which are BK-spaces.
Keywords: sequence space; BK-space; matrix mapping; sequence spaces of non-absolute type